2009
DOI: 10.1002/hed.21045
|View full text |Cite
|
Sign up to set email alerts
|

Increased mRNA expression of ADAMTS metalloproteinases in metastatic foci of head and neck cancer

Abstract: Our findings suggest a metastasis model proposing accumulation of a subtype of cancer cells with high metastatic capacity within heterogenous primary tumor cell population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 23 publications
2
35
0
8
Order By: Relevance
“…Downregulation of ADAMTS8 has been found in some tumors, such as brain tumors (14), breast carcinoma (9), non-small cell lung carcinoma (15), head and neck squamous cell carcinoma (16), and pancreatic cancer (17), whereas its expression in other common solid tumors including nasopharyngeal (NPC), esophageal squamous cell (ESCC), gastric, colorectal (CRC), renal (RCC), and cervical carcinomas remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of ADAMTS8 has been found in some tumors, such as brain tumors (14), breast carcinoma (9), non-small cell lung carcinoma (15), head and neck squamous cell carcinoma (16), and pancreatic cancer (17), whereas its expression in other common solid tumors including nasopharyngeal (NPC), esophageal squamous cell (ESCC), gastric, colorectal (CRC), renal (RCC), and cervical carcinomas remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that CA repeat contraction in the microsatellites located in the ADAMTS9 promoter may block RNA polymerase binding to the ADAMTS9 promoter. If this scenario is correct, cancer-related gene expression, such as that of ADAMTS9, in tumors would decrease (15,16), and lower matrix metalloproteinase activity would translate into a reduced ability to invade lymphatic vessels and metastasize. Porter et al reported that the expression of ADAMTS9 in breast cancer tissues was down-regulated with respect to noncancerous breast tissues and uncovered a potential association between ADAMTS9 and breast cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several matrix metalloproteinases are known to contribute to the invasion and traversal of the extracellular matrix in metastatic spreading. Together with ADAMS, the ADAMTS proteinases have been shown to play a role in cancer development and progression (16). Because ADAMTS9 is a matrix metalloproteinase, ADAMTS9 gene expression may be related to tumor progression and metastatic spreading.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Briefly, mRNA coding for CTGF, TGF-b1 and 18s rRNA was quantified using the LightCycler rapid thermal cycler system (Roche Diagnostics, Lewes, UK) according to the manufacturer's instructions. A typical protocol took approximately 45 min and included a 10-min denaturation step, followed by 40 cycles of denaturation at 95 1C for 10 s, annealing at 65 1C for 10 s and extension at 72 1C for 20 s.…”
Section: Quantitative Real-time Reverse Transcription Pcr (Rt-pcr) Anmentioning
confidence: 99%